2017
DOI: 10.1038/s41598-017-10642-1
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged fasting elicits increased hepatic triglyceride accumulation in rats born to dexamethasone-treated mothers

Abstract: We investigated the effect of dexamethasone during the last week of pregnancy on glucose and lipid metabolism in male offspring. Twelve-week old offspring were evaluated after fasting for 12-hours (physiological) and 60-hours (prolonged). Physiological fasting resulted in glucose intolerance, decreased glucose clearance after pyruvate load and increased PEPCK expression in rats born to dexamethasone-treated mothers (DEX). Prolonged fasting resulted in increased glucose tolerance and increased glucose clearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 47 publications
5
20
1
1
Order By: Relevance
“…As reported by us in previous studies [ 16 , 33 ], rats born to DEX-treated mothers displayed reduced birth weight (18% lower than CTL; p = 0.033) ( Figure 1 A). The body weights of the 40 h fasted offspring with 160 days of age were influenced by both in utero exposure to DEX and treatment with 10% fructose ( p < 0.0001 and p = 0.0002, respectively).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As reported by us in previous studies [ 16 , 33 ], rats born to DEX-treated mothers displayed reduced birth weight (18% lower than CTL; p = 0.033) ( Figure 1 A). The body weights of the 40 h fasted offspring with 160 days of age were influenced by both in utero exposure to DEX and treatment with 10% fructose ( p < 0.0001 and p = 0.0002, respectively).…”
Section: Resultssupporting
confidence: 84%
“…In utero exposure to DEX is well known for programming metabolic changes in the adult offspring of rats. The metabolic imprinting caused by excessive exposure to DEX during fetal life is hallmarked by glucose intolerance, increased whole-body gluconeogenesis, and upregulation of PEPCK expression in the liver [ 17 , 33 , 34 ]. Recently, we have also described that in utero exposure to DEX exacerbates hepatic steatosis caused by fructose consumption during adult life [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the DOHaD concept has initially focused on the nutritional status during pregnancy, fetal overexposure to glucocorticoids—a common feature of maternal undernutrition, maternal stress, and poor fetal blood supply—has also been shown to play a central role in the metabolic programming of the offspring [15]. For example, previous studies demonstrated that in utero dexamethasone (DEX) exposure favors hepatic steatosis in the adult offspring subjected to either food deprivation or excess fat intake [16,17,18]. It is also worth noting that exposure to antenatal glucocorticoids is far from being an exclusively experimental condition, since its use is a common medical approach for increasing the pre-term survival rate [19].…”
Section: Introductionmentioning
confidence: 99%
“…RNA purity (260/280 and 260/230 ratios) and concentration were calculated using a NanoDrop 2000 spectrophotometer (Thermo Scientific, Waltham, MA, USA) and subjected to poly(A) tailing and reverse transcription with an annealed adaptor (5 -GGCCACGCGTCGACTAGTAC(T)12-3 ) as previously described [21]. PCRs were conducted using KAPA SYBR ® FAST qPCR Master Mix (Kapa Biosystems, Inc., Boston, MA, USA) in a StepOnePlus Real-Time PCR System (Applied Biosystems, Foster City, CA, USA), using adhesive-sealed plates.…”
Section: Rna Extraction and Mrna And Mirna Detectionsmentioning
confidence: 99%